PROFESSIONAL TRAINING OF ELECTRONICS ENGINEERS: COMPARATIVE STUDY METHODOLOGY - Pavlenko, Olha (Educological discourse, 2020)
The study aims to describe the methodology for a comparative study of US and Ukrainian higher education institutions, namely with regard to the professional training of electronics engineers. Although applying international experiences in training students of higher education institutions is becoming more widely accepted by Ukrainian higher education institutions, few studies attempted to explore the impact of leading US institutions’ best engineering education practices on Ukrainian higher engineering education. It is suggested that comparing professional training of electronics engineers in US and Ukrainian higher education contexts should address the feasibility and procedures for US experience implementation. Thus, this article determines the levels of comparative pedagogical analysis of professional training of electronics engineers i.e. conceptual, organizational and methodological, content and technological. In addition, invariant tasks of comparative pedagogical research are proposed. In particular, they include analysis and comparison of concepts, provision of procedures and comparison criteria, description of research stages, applying the discovered US educational experience to the Ukrainian context, development of recommendations for educational policy with regard to the modernization of higher education. The comparative analysis of concepts has identified the equivalents in the educational contexts of two countries as well as shown the need for introducing some new concepts into Ukrainian engineering education terminology. Criteria introduced by the leading international, US and Ukrainian ranking systems, Accreditation Board for Engineering and Technology enabled the selection of 43 appropriate higher engineering institutions. The findings reveal that US educational experience allows Ukrainian institutions that train electronics engineers to find optimal solutions to solve these problems and outline promising areas for applying the US experience. Comparative study of two educational systems is of undeniable practical importance, particularly with respect to the modern period of Ukrainian higher engineering education reforms. Keywords: electronics engineer; engineering education; comparative study; higher education institution; professional training; Ukrainian higher education; US higher education.